Analisis Implementasi Pengelolaan Dana Kapitasi JKN oleh Puskesmas di Kabupaten Pasaman Barat - wilia nespita (Jurnal Ipteks Terapan, 2019)
AbstractBackground: The total of remaining funds that accumulate in the public health center  account will cause various impacts, especially the useles funds. The capitation fund was very prone to be frauded, so that need  special actions related to the management of this capitation fund. Objective: This study aimed to determine the input components that support the management of capitation funds by public health center in West Pasaman Regency. Method: Qualitative research study with semi-structured interviews, document review and observation with 9 informants. They were head of regency, Regional People's Representative Assembly,  Health Departement and 2 sample from Public Health Center. Results: Management of capitation funds by Public Health Center in West Pasaman Regency was not optimal yet. The cause can be seen in the input component, which is the change in policy used after becoming a BLUD, so the public health center need time to adjut. The main manager who the treasurer was not yet equipped with knowledge about regional financial accounting and management, and infrastructure such as special rooms that were not available yet. Conclusion: The capitation fund management in Public Health Center needs to be improved by increasing the capacity of financial management personnel and completing infrastructure that is not available yet. Keyword : Capitation Funds, Management, National Health Insurance  AbtrakLatar Belakang : Jumlah dana sisa yang menumpuk di rekening puskesmas akan menimbulkan berbagai dampak terutama munculnya dana yang tidak termanfaatkan atau dana sisa. Dana kapitasi ini sifatnya sangat rawan untuk disalah gunakan sehingga perlu adanya tindakan yang khusus terkait pengelolaan dana kapitasi ini. Tujuan : Untuk mengetahui komponen input yang mendukung dalam pengelolaan dana kapitasi JKN oleh puskesmas di Kabupaten Pasaman Barat. Metode : Penelitian kualitiatif dengan wawancara semi-terstruktur, telaah dokumen dan observasi dengan jumlah informan 9 orang yang terdiri dari Bupati, DPRD, Dinas Kesehatan dan 2 Puskesmas sampel. Hasil : Pengelolaan dana kapitasi oleh puskesmas di Kabupaten Pasaman Barat belum optimal. Penyebabnya dapat dilihat komponen input yaitu adanya perubahan kebijakan yang digunakan setelah menjadi BLUD, sehingga puskesmas butuh waktu untuk penyesuaian, tenaga pengelola utama yaitu bendahara yang belum dibekali ilmu tentang akuntasi dan pengelolaan keuangan daerah, dan prasarana seperti ruangan khusus yang belum tersedia. Kesimpulan : pengelolaan dana kapitasi JKN oleh puskesmas perlu ditingkatkan dengan cara peningkatan kapasitas tenaga pengelola keuangan dan melengkapi prasarana yang belum tersedia. Keywords: Dana Kapitasi, Pengelolaan, JKN